Relationship of Meteorological Variables with the Concentration of Various Tree Pollen Types in Madrid (Spain) - Javier Chico-Fernández; Esperanza Ayuga-Téllez (Applied Sciences)
This study analyzes the behavior of airborne pollen in relation to meteorological parameters. It may be helpful to understand the consequences of this interaction on the health of the population of Madrid in the form of respiratory allergic pathologies. To this end, a multivariate analysis was carried out using Spearman’s linear correlation coefficient between the concentrations in the Madrid atmosphere of six types of tree pollen (Cupressaceae, Olea, Platanus, Pinus, Ulmus and Populus) and each of the six meteorological variables: relative humidity, precipitation, temperature, wind, radiation and insolation. The meteorological parameters most correlated with pollen types, with monthly values, are temperature and insolation, followed by radiation and relative humidity. In addition, there are more significant correlations of meteorological variables with Cupressaceae, Olea, Pinus and Platanus pollen types. Radiation is the meteorological parameter with the highest ρ values, especially with Olea, with ρ > 0.8. Wind is the only variable with significant correlations, all of them positive, with pollen types. The number of statistically significant results obtained from daily values is lower compared to monthly values, and only with Populus, Cupressaceae and Olea. The inter-relationship of meteorological variables with pollen grains can lead to an increase in the number of cases of pollinosis, when there are significant positive correlations.